Mutualistic Interaction Between Mealy Bugs And Ants Towards The Development Of A Novel Sugar Ant Bait - Jong, Zheng Wei (2022)
Mealy bugs are important honeydew producers, and many have developed mutualistic interaction with ants. Honeydew appears to be attractive to many ant species and it supplies constant carbohydrates to meet ant vast metabolic requirement. The exploration of the mutualistic interactions and the honeydew content provide new insights on the interactions and potential control of ants through the attractant in honeydew. Hence, this thesis focuses on the mutualistic interaction between mealy bugs and ants in conjunction with the development of a novel sugar ant bait.